Atherothrombosis‐on‐Chip: A Site‐Specific Microfluidic Model for Thrombus Formation and Drug Discovery. Issue 7 (4th June 2022) - Akther, Fahima; Zhang, Jun; Tran, Huong D. N.; Fallahi, Hedieh; Adelnia, Hossein; Phan, Hoang‐Phuong; Nguyen, Nam‐Trung; Ta, Hang Thu
Abstract: Atherothrombosis, an atherosclerotic plaque disruption condition with superimposed thrombosis, is the underlying cause of cardiovascular episodes. Herein, a unique design is presented to develop a microfluidic site‐specific atherothrombosis‐on‐chip model, providing a universal platform for studying the crosstalk between blood cells and plaque components. The device consists of two interconnected microchannels, namely main and supporting channels: the former mimics the vessel geometry with different stenosis, and the latter introduces plaque components to the circulation simultaneously. The unique design allows the site‐specific introduction of plaque components in stenosed channels ranging from 0% to above 50%, resulting in thrombosis, which has not been achieved previously. The device successfully explains the correlation between vessel geometry and thrombus formation phenomenon as well as the influence of shear rate on platelet aggregation, confirming the reliability and the effectiveness of the design. The device exhibits significant sensitivity to aspirin. In therapeutic doses (50 × 10 −6 and 100 × 10 −6 m ), aspirin delays and prevents platelet adhesion, thereby reducing the thrombus area in a dose‐dependent manner. Finally, the device is effectively employed in testing the targeted binding of the RGD (arginyl‐glycyl‐aspartic acid) labeled polymeric nanoparticles on the thrombus, extending the use of the device to examine targeted drug carriers. Abstract : This study reports a real‐time site‐specific atherothrombosis‐on‐chip model. The chip consists of two interconnected channels: the main channel for mimicking vessel geometry and the supporting channel to introduce plaque components to the circulation. The chip provides a suitable platform to study the influence of vessel geometry and shear rate on the thrombus formation phenomenon, along with drug screening and discovery.